Age Peculiarities of Nitrogen Oxide Role in Animal Adaptation Mechanisms to Rhythmic Cold Effects Report 2. Content of NO Metabolism Final Products in Brain Cortex and Hypothalamus of Young and Aged Animals After Rhythmic Cold Effects - Babijchuk, V. G. (Problems of Cryobiology and Cryomedicine, 2007)
The experimental results on studying the effect of rhythmical cold effects (RCEs) on the content of NO (nitrites) metabolism final products in brain cortex and hypothalamus of young and aged rats are presented. Nitrite content in brain cortex of young rats was shown to be higher than in aged ones. Applying the blockers of NO-synthase synthesis suppresses their production but L-arginine activator increases it in rats of both age groups. Rhythmical cold effects contribute to the nitrite content augmentation. There was assumed about an important role of blood-brain barrier in animal adaptation to RCEs as well as NO as intracellular mediator, participating in regulation of vegetative functions.